Model Tentang Kemandirian Komisi Pemilihan Umum Dalam Pemilihan Gubernur, Bupati, Dan Walikota (Perspektif Undang-Undang Nomor 10 Tahun 2016 dengan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945) - TONIDAYA, RAHMAT SETIAWAN; , Prof. Dr. Harun, SH., M.Hum; , Wardah Yuspin, SH., M.Kn., Ph.D (2017)
The enactment article of 9 point a, law number 10 year 2016 states "Duties and Authority General Election Commissions in the conduct of elections of governors, regents and mayors include: (a) Establishing and arrange General Election Commission rules and technical guidelines for each stage of the election after consultation with the House of Representatives and the Government in the forum of a hearing decision will be binding", shows the involvement of the executive and the legislative is so central and decisive in authority of the General Election Commissions in drafting and establishing rules and technical guidelines for each stage. Such provisions could potentially threaten the independence of the Commission on Elections as an independent state agency. Research type used for this study is qualitative descriptive. This study uses an content analysis approach, the method of analysis is to explain material juridical legal events are researched and written on the basis of the use of primary data sourced from interviews and secondary data and also the comparative approach is done by using a comparative study of law. As for the results of this research are, results of the research is descriptive law that is the implementation of the independence of the Commission in accordance with act number 10 year 2016, test the independence of the Commission in accordance with act number 10 year 2016 if compared with the Constitution and the results of research conducted with qualitative analysis that models the independence of the Commission in accordance with act number 10 year 2016 and also uses comparative law in other countries.